WOMEN TEACHERS’ EDUCATION IN GREECE, BULGARIA, AND TURKEY DURING THE 19TH CENTURY: PARALLEL PATHS AND INTERACTIONS - Vassilis Foukas (İmgelem)
The Balkans have a long history of cultural and religious diversity, with Greeks, Bulgarians, and Ottomans coexisting within the same geographical area and state system. Despite differences, their social, economic, and cultural lives were intertwined. Over time, unique national ideologies emerged, giving rise to independent and diverse nation-states. The exchanges between these groups continued even after the Ottoman period amidst the rise of secessionism and nationalist debate. The importance of secular-national educational systems grew during this time, as monastic schools declined. That led us a remarkable outcome. It underscored the crucial intersections and essential congruence in our pedagogical perspectives, the systematic arrangement of our concepts, and the instructional materials we employ. During the 19th century, the first public girls’ schools and women associations established, as well as women journals and the recognition of teaching as a profession for women. Greece, Bulgaria, and Turkey have followed parallel paths towards full social acceptance of the teaching profession, with the women teachers’ education and the first female teachers emerging first in Greek-speaking populations with a national and Western bourgeois consciousness. This paper examines the women teachers’ education in these countries during the 19th century, identifying the parallel paths and interactions in the organization and content of their schools within a broader educational, socio-economic, and ideological context.